1999
DOI: 10.1038/sj.bjp.0702721
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels involved in the inhibition of acetylcholine release by presynaptic muscarinic receptors in rat striatum

Abstract: 1 The mechanism of the inhibitory action of presynaptic muscarinic receptors on the release of acetylcholine from striatal cholinergic neurons is not known. We investigated how the electrically stimulated release of [ 3 H]-acetylcholine from superfused rat striatal slices and its inhibition by carbachol are aected by speci®c inhibitors of voltage-operated calcium channels of the L-type (nifedipine), N-type (o-conotoxin GVIA) and P/Q-type (o-agatoxin IVA). 2 The evoked release of [ 3 H]-acetylcholine was not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 54 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…At the same time, this also may explain the specific binding of LEV in rat central nervous system (CNS) (40), where N‐type channels (α1B) are principally expressed in comparison with other tissues (41). The predominant action of LEV on discrete areas of rat brain such as striatum (42), where N‐type channels compose the main subpopulation of calcium channels (43), was shown. It also was shown that another AED, lamotrigine (LTG; Lamictal) also can exert its effect through inhibition of presynaptic N‐type Ca 2+ channels (44–46).…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, this also may explain the specific binding of LEV in rat central nervous system (CNS) (40), where N‐type channels (α1B) are principally expressed in comparison with other tissues (41). The predominant action of LEV on discrete areas of rat brain such as striatum (42), where N‐type channels compose the main subpopulation of calcium channels (43), was shown. It also was shown that another AED, lamotrigine (LTG; Lamictal) also can exert its effect through inhibition of presynaptic N‐type Ca 2+ channels (44–46).…”
Section: Discussionmentioning
confidence: 93%
“…In central neurons, evoked vesicular release of ACh is dependent on calcium entry into the presynaptic terminal through voltage‐gated calcium channels (Dolezal and Tucek, 1999). Ca V 2.2 channels have been demonstrated in cholinergic terminals on adult rat myenteric neurons (Kirchgessner and Liu, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition was high in slices with functional N-type channels. Thus, it was concluded that the N-type calcium channel may contribute to the stimulation of acetylcholine release in rat striatum [ 97 ].…”
Section: Neuropeptides From Marine Sourcesmentioning
confidence: 99%